Bioactivity of ionic liquids - Ferraz, Ricardo (2021)
Ionic liquids (ILs) were discovered a century ago, but it was only three decades ago that they started to catch the attention of the scientific commu- nity. ILs are defined as organic salts composed of an organic cation and an organic or inorganic anion2,3 that are stable below their melting point.